Chapter 2 Working Together: Interior Architecture creating with the community - Lommerse, Marina (Paper and Pencil, 2011)
This chapter presents ideas, frameworks and principles for Community Engagement and Interior Architecture. Community Engagement is defined as a cooperative process of working with people to address their wellbeing, crossing disciplinary boundaries, and using multiple knowledge from inside and outside the community. Community Engagement is predicated on the consent and active participation of the community whose social capital, processes or environments are being considered, thereby playing a vital role in social sustainability. Examples are drawn from a review of published and unpublished case studies from those whose work is engaged with community. The reflection suggests possible answers to questions such as: what is the value of Community Engagement in relation to social sustainability? How can interior architecture be meaningfully involved?